Properties and drivers of fast interplanetary shocks near the orbit of the Earth (1995–2013). Issue 6 (17th June 2015) - Kilpua, E. K. J.; Lumme, E.; Andreeova, K.; Isavnin, A.; Koskinen, H. E. J.
Abstract We present a comprehensive statistical analysis spanning over a solar cycle of the properties and drivers of traveling fast forward and fast reverse interplanetary shocks. We combine statistics of 679 shocks between 1995 and 2013 identified from the near‐Earth (Wind and ACE) and STEREO‐A observations. We find that fast forward shocks dominate over fast reverse shocks in all solar cycle phases except during solar minimum. Nearly all fast reverse shocks are driven by slow‐fast stream interaction regions (SIRs), while coronal mass ejections (CMEs) are the principal drivers of fast forward shocks in all phases except at solar minimum. The occurrence rate and median speeds of CME‐driven fast forward shocks follow the sunspot cycle, while SIR‐associated shocks do not show such correspondence. The strength of the shock (characterized by the magnetosonic Mach number and by the upstream to downstream magnetic field and density ratio) shows relatively little variations over solar cycle. However, the shocks were slightly stronger during the ascending phase of a relatively weak solar cycle 24 than during the previous ascending phase. The CME‐ and SIR‐driven fast forward shocks and fast reverse shocks have distinct upstream solar wind conditions, which reflect to their relative strengths. We found that CME‐driven shocks are on average stronger and faster, and they show broader distributions of shock parameters than the shocks driven by SIRs.